A multidisciplinary analytical approach to the identification of both modifiable and non-modifiable risk factors of dementia - Willoughby, Kathleen Angela, author; Davalos, Deana, advisor; Rojas, Don, committee member; Malinin, Laura, committee member; Cleveland, Jeanette, committee member (Colorado State University. Libraries, 2021)
In recent decades, dementia has become a growing global epidemic. As people are living longer, the number of individuals diagnosed with dementia has risen exponentially. Alzheimer's disease, the most common form of dementia, presently afflicts more that 5.4 million Americans (Thies et al., 2011). Though great strides have been made in dementia research, there is still much to be done to better pin-point disease risk and ameliorate decline and related symptom progression. This dissertation will focus on the efficacy of early intervention and risk factor identification as a first line of defense in staving off dementia progression. Within the B Sharp community-arts engagement program, we will evaluate domain-specific changes in older adult cognition over an acute and extended-duration timespan. Within the Alzheimer's Disease Neuroimaging Initiative, we will identify relevant risk factors associated with the consistent acceleration of cognitive decline as well as the slowing of such decline. As these proactive treatment approaches are more fully understood, better strategies for healthy aging can be implemented at both a generalized and individual level.